2009
DOI: 10.1021/bi901216s
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of the Distal Hydrogen Bond Network to the Exogenous Ligand in Substrate-Bound, Resting State Human Heme Oxygenase

Abstract: Mammalian heme oxygenase, HO, possesses catalytically implicated distal ordered water molecules within an extended H-bond network, with one of the ordered water molecules (#1) providing a bridge between the iron-coordinated ligand and the catalytically critical Asp140, that, in turn, serves as an acceptor for the Tyr58 OH H-bond. The degree of H-bonding by the ligated water molecule and the coupling of this water molecule to the H-bond network are of current interest and are herein investigated by 1 H NMR. 2D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…In contrast, the regiospecificity of classic HOs is achieved by steric restriction of the hydroperoxy ligand that forms during heme oxidation so that only the α-meso carbon is accessible for hydroxylation (6,8,9). In addition, the distal heme pockets of classic HOs also possess a group of ordered water molecules that direct protons to the catalytic center to stabilize the reactive hydroperoxy intermediate (8,(10)(11)(12)(13)(14). This water network is proposed to be required for catalysis by all classic HOs (11,(15)(16)(17)(18), but it is absent from the active sites of IsdG and IsdI (5,19).…”
mentioning
confidence: 99%
“…In contrast, the regiospecificity of classic HOs is achieved by steric restriction of the hydroperoxy ligand that forms during heme oxidation so that only the α-meso carbon is accessible for hydroxylation (6,8,9). In addition, the distal heme pockets of classic HOs also possess a group of ordered water molecules that direct protons to the catalytic center to stabilize the reactive hydroperoxy intermediate (8,(10)(11)(12)(13)(14). This water network is proposed to be required for catalysis by all classic HOs (11,(15)(16)(17)(18), but it is absent from the active sites of IsdG and IsdI (5,19).…”
mentioning
confidence: 99%
“…NMR, in combination with other spectroscopies and molecular dynamics calculations, has been extensively used to learn about the heme degradation mechanism, both via the characterization of the heme electronic structure and degradation products with extensive use of 13 C-NMR on selectively enriched hemes and via the definition of conformational and dynamical properties of the polypeptide part with the classical bio-NMR approaches. [98][99][100][101][102][103][104][105] Other proteins that convey heme across the bacterial cells are the ironregulated surface determinant proteins (IsD) from gram-positive bacteria. 106 IsdC in Staphylococcus aureus is the protein through which the heme passes across the cell wall; its NMR structure in the apo form and in the complex with the zincsubstituted protoporphyrin IX has been solved.…”
Section: Interaction With the Heme Cofactormentioning
confidence: 99%
“…[18-20] In mammalian HOs [11, 12] and HmuO, [8, 9] a key homologous Asp (140 in mammalian HO, 136 in HmuO) is at the center of the coupling between the exogenous ligand and the distal H-bond network via the ordered water molecules. In spite of significant sequence [5] and structural [8, 9, 11] homology, particularly in the H-bond network, [18, 19] the Asp mutation completely abolished activity in mammalian HO, [21, 22] but only reduced it to one-half in HmuO.…”
Section: Introductionmentioning
confidence: 99%
“…[24] A simple system for examining the coupling of the exogenous ligand to the H-bond network through the ordered water molecules is the equilibrium between the resting-state, high-spin, aquo, and the low-spin, hydroxo complexes, where simple deprotonation of the ligated water within a conserved molecular structure converts the H-bond donor ligated water molecule into an H-bond acceptor hydroxide ligand. A recent 1 H 2D NMR study [20] has shown that, upon deprotonation of the axial water in human HO, hHO-1, the low-field bias of the Tyr58 OH, which is a strong H-bond donor to the catalytically critical Asp140, moves ~2.7 ppm to lower field, suggesting a very substantial increase in the Tyr58 H-bond donor strength in the hydroxide complex. However, the chemical shift changes cannot be directly related to changes in H-bonding, since both complexes are paramagnetic and protons can experience significant dipolar shifts, [25, 26] δ dip , within ~12Å of the iron.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation